IDENTIFICATION OF HIGH-TEMPERATURE TOLERANCE OF SOME POTATO VARIETIES BASED ON STRESS TOLERANCE INDICE AND CLUSTER ANALYSIS - Miranti Dian Pertiwi; Endang Sulistyaningsih; Rudi Hari Murti; Benito Heru Purwanto (Agric, 2022)
Potato self-sufficiency in Indonesia faces three main problems: rising air temperatures, limited availability of low-temperature land suitable for potato cultivation, and lack of high-temperature tolerant potato varieties. Therefore, it is necessary to identify the tolerance of potato variety to high-temperature. This research was conducted in two locations: the optimum temperature location and the high-temperature location, using nine varieties, are Agria, Andina, Amabile, Cingkariang, Granola L, Granola K, Margahayu, Olympus, and Tedjo-MZ. The study design uses a split plot with three replications. Differences in temperature as the main plot and varieties as subplots. Parameters observed were air temperature, growth, and yield of potato tubers. The analysis carried out were the Stress Sensitivity Index (SSI), Stress Tolerance Index (STI), Yield Stability Index (YSI), and Cluster Analysis. The results showed that there were no tolerant to high-temperature varieties. Based on the STI, only Olympus was a medium tolerant of high temperatures. Based on the Stress Sensitivity Index (SSI), four varieties are moderately susceptible to high temperatures (Olympus, Andina, Cingkariang, and Margahayu). The YSI analysis shows the same results as the SSI. The cluster analysis results showed harmony between the results of the stress index analysis and cluster analysis. Nine varieties had a high similarity (87.3%), meaning that all varieties had the same characteristics and less tolerance to high temperatures. Olympus was the more tolerant variety to high temperatures, followed by Andina, Cingkariang, and Margahayu. The four varieties consider promising potato lines in high-temperature areas.